Recognition of Local DNA Structures by p53 Protein - Brázda, Václav; Coufal, Jan (International journal of molecular sciences, 2017)
p53 plays critical roles in regulating cell cycle, apoptosis, senescence and metabolism and is commonly mutated in human cancer. These roles are achieved by interaction with other proteins, but particularly by interaction with DNA. As a transcription factor, p53 is well known to bind consensus target sequences in linear B-DNA. Recent findings indicate that p53 binds with higher affinity to target sequences that form cruciform DNA structure. Moreover, p53 binds very tightly to non-B DNA structures and local DNA structures are increasingly recognized to influence the activity of wild-type and mutant p53. Apart from cruciform structures, p53 binds to quadruplex DNA, triplex DNA, DNA loops, bulged DNA and hemicatenane DNA. In this review, we describe local DNA structures and summarize information about interactions of p53 with these structural DNA motifs. These recent data provide important insights into the complexity of the p53 pathway and the functional consequences of wild-type and mutant p53 activation in normal and tumor cells.
Keywords: nádorový supresorový protein p53; konformace nukleové kyseliny; p53 protein; Nucleic Acid Conformation; Protein Binding; DNA; protein-DNA interactions; Tumor Suppressor Protein p53; zvířata; vztahy mezi strukturou a aktivitou; Humans; Binding Sites; B-DNA; vazba proteinů; DNA, B-Form; Structure-Activity Relationship; local DNA structures; vazebná místa; lidé; Animals